Artistic experiment as the basis of the storytelling in the novel «Company K» by W. March - Tratsiak, Zoya I. (Journal of the Belarusian State University. Philology, 2024)
The novel «Company K» by W. March, dedicated to the experience of an American in the World War I, is under consideration. The discreteness of the storytelling is noted. The story of 113 infantry characters acquires artistic integrity, forming a so-called collective hero – a literary subject that summarises individual small complementary episodes of human existence during the war. It allows the writer to approach the embodiment of the global armed conflict in a comprehensive manner. Typological parallels with Western European prose about the events of 1914 –1918 have been studied. The anti-war pathos of the work is emphasised, predetermined by the W. March’s biography as a military man. The main semantic dominants of the storytelling are analysed (the creation and destruction of a letter to the mother of a murdered man, the execution of German prisoners, the death of a soldier who got rid of his insignia to preserve the right to anonymity). Attention is drawn to the author’s experiments with the word, which was supposed to embody adequately the sound image of the battle or the feelings of a person who survived a gas attack.